THE EFFORTS TO IMPROVE STUDENTS'ABILITY TO WRITE EXPOSITION TEXT WITH DISCOVERY LEARNING METHOD BY CLASS X (TENTH) STUDENTS OF SMA NEGERI 1 HILIMEGAI - Ndruru, Noverianus Siduhu (Al'Adzkiya Journal, 2020)
ABSTRACT This study aims to improve the exposition writing skills of class X SMA Negeri 1 Hilimegai by using discovery learning method. The use of this learning model is expected to make it easier for students to understand the material and be able to write exposition text so that students' abilities increase. Through discovery learning model, improvement can be seen both in process and product. This research was conducted at SMA Negeri 1 Hilimegai. The research subjects were 23 teachers and students of class X SMA Negeri 1 Hilimegai. The implementation of this research is divided into two cycles, each cycle carried out in two meetings. Research data obtained through. The data collection methods used in this research are the observation method, the test method, and the questionnaire method. And also in the form of student assignments and photo documentation during learning. The data analysis technique was carried out by using a qualitative descriptive technique. The product success criteria in this study can be seen from the change in value that is better in each cycle. The success of this research is seen from two criteria, namely the success of the process and the product. The research results obtained are as follows. First, the use of discovery learning models can improve the quality of learning exposition writing in students. This is shown in the improvement of the process in the aspect of learning situations, students are more focused on learning, students are also more active in groups, and learning exposition writing becomes more enjoyable. Second, the use of discovery learning models can improve the results of exposition writing skills. This can be seen in the increase in the results obtained by students from cycle I and cycle II. Overall, at the end of cycle II, all aspects and criteria for exposition writing had increased significantly. Based on the results of this study, it can be concluded that the use of the discovery learning model was successful and was able to improve the exposition writing skills of class X SMA Negeri 1 Hilimegai.